Effectiveness of sensory re-education as adjunct therapy to conservative intervention program on hand function in the treatment of moderate to severe carpal tunnel syndrome: a quasiexperimental study / Anwar Abdullah - Abdullah, Anwar (2021)
Introduction: Sensory Re-education (SR) is one of the treatment options for the ongoing discomfort and poor tactile gnosis encountered by clients with Carpal Tunnel Syndrome (CTS). However, there is a little published study on investigating the effectiveness of the SR program with the standard conservative treatment as compared to the option of utilizing the SR program following the surgical procedure. Purpose: This study was divided into two-phase, i.e., Phase One: was aimed to determine the psychometric properties of the cross-cultural Malay version of the Boston Carpal Tunnel Questionnaire (M-BCTQ) as a preparation for the next phase; Phase Two: was aimed to evaluate the effects of the SR program as an adjunct to standard conservative treatments in improving hand function of clients with moderate to severe CTS as compared to standard conservative treatments alone. Methodology: A cross-sectional study in Phase One and a quasi-experimental study in Phase Two was conducted in the Hand and Microsurgery Unit at Selayang Hospital, Selangor. In the Phase One study, 65 clients with CTS and ten professional therapists were recruited to participate in the reliability and validity cross-sectional study of MBCTQ. While, in Phase Two, 108 clients were allocated to either SR program and standard conservative treatments (SR+SCT) group (n=54) or standard conservative treatments (SCT) group (n=54) for eight weeks treatment period. A total of 96 clients completed a 4-week and 8-week follow-up. The primary outcome measures in this study were the Semmes Weinstein Monofilament (SWM), Locognosia, Static two-point discrimination (2PD) and the M-BCTQ. Secondary outcomes were handgrip strength, Visual Analog Scale (VAS), and Purdue Pegboard test for fine motor function. Results: M-BCTQ has been verified to have excellent test-retest reliability with ICCs value of 0.837 for Symptom Severity Scale (SSS) and 0.893 for the Functional Status Scale (FSS). A strong correlation was found with the Malay version of Disability of Arm, Shoulder and Hand Questionnaire (MVDASH) as Spearman correlation for construct validity was 0.791 for SSS and 0.831 for FSS. While, in Phase Two study, significant group differences in favour to SR+SCT group was shown at 4-week and 8- week follow-up for the primary outcomes measures involves of Locognosia (p=0.001, p=0.027), Static 2PD (p<0.001, p<0.001), and M-BCTQ for Overall (p=0.001, p<0.001), and SSS (p<0.001, p<0.001). For the secondary outcome, only Purdue Pegboard test in Left hand (p=0.025, p=0.028) and Assembly (p<0.001, p<0.001) subtest were shown significant group differences at 4-week and 8-week follow-up. Repeated measure ANOVA showed that there was a significant main effect of all outcome measures within both groups excepts for SWM score and Static 2PD in the SCT group. Although the analysis from linear mixed model has confirmed that gender and severity of numbness were found influenced the effect of the intervention particularly in Purdue Pegboard test, the SR+SCT group showed better improvement in all outcome measures as compared to SCT group. Conclusion: This study has validated the M-BCTQ as an evaluation tool for CTS’s clients with Malay speaking population in Malaysia. This study also highlighted the use of SR program as an adjunct to standard conservative treatments improved the hand function and symptoms of clients with moderate to severe CTS as compared to standard conservative treatments alone. Findings from this study have had a significant impact on the body of knowledge and practice of occupational therapy in hand therapy on the management of CTS via a non-pharmacological and non-surgery approach.